Transport properties of palm oil fuel ash-based high-performance green concrete subjected to steam curing regimes. (June 2022) - Zeyad, Abdullah M.; Megat Johari, Megat Azmi; Abadel, Aref; Abutaleb, Ahmed; Mijarsh, M.J.A.; Almalki, Ali
Abstract: Effect of steam curing regimes on high-performance green concrete (HPGC) has been studied. The concrete was steam cured under three different steam curing regimes with temperatures of 50 °C, 65 °C, and 80 °C and durations of 6, 11, and 16 h. In addition, the replacement level of palm oil fuel ash (U-POFA), which was an experimental variable, was 0%, 20%, 40%, and 60% by weight of cement. The compressive strength (CS), initial surface absorption, porosity, water absorption, gas permeability, and water permeability were tested at 3, 7, 28, 90, 180, and 360 days. The results of the study showed that the utilization of U-POFA in HGPC led to a reduction at the early age CS of the HPGC up to 3 days. However, concrete mixes made with U-POFA showed higher CS at 28–360 days. U-POFA incorporation improved the transport properties of the concrete, with U-POFA60 mix exhibiting the most significant improvement. While application of higher curing temperature tends to impair the properties of the HPGC, longer steam curing period appears to provide a positive effect than shorter duration. The use of U-POFA lessens the negative impact of steam curing on the long-term transport properties of the HPGC. The use of U-POFA at 60% of the weight of the cement achieved CS of 115.8 and 116.9 MPa at 360 days under normal and steam curing, respectively. At the same time, the water absorption was 3.13% and 2.29% under normal and steam curing, respectively.